The court charade - Kerascoët; Vesco, Flore 1981- (Abrams ComicArts, 2026)
"This lighthearted, sharply witty adult fairy tale is a delightful and quirky take on toxic workplaces, with a dash of Puss in Boots-style antics and a little romance thrown in for good measure. Serine is a poor but plucky daughter of a sickly nobleman who must make her way in the royal court to avoid being married off once her father dies. Although she is illiterate and owns only one dress, she manages to charm her way into the fickle queen's good graces--but the royal court is not a kind place for a country bumpkin. Silly, sweet Serine must smarten up if she wants to survive the queen's fits of pique, the court ladies' gossip, and the royal advisor's evil schemes. With nothing but her wits and the help of the friendly, handsome torturer's apprentice, can she find a way to save her job, save the kingdom, and find true love along the way? Or will she be forced to play the fool?"--Amazon.